2020
DOI: 10.5829/ijee.2020.11.02.11
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Numerical Study of the Performance of a Small Combined Savonius-Darrieus Vertical Wind Turbine

Abstract: Energy crisis and global warming have encouraged the use of renewable energy resources such as wind power. Among different types of wind turbines, vertical axis wind turbines can be easily installed in residential areas. In this study, a computational fluid dynamics analysis was performed to predict the performance characteristics of three configurations of small vertical axis wind turbines. For this purpose, an shear stress transport k-omega turbulent model and a rotating frame of reference were employed. Ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This will require changes in the energy supply infrastructure. However, if all transport vehicles can run on batteries (electric and/or hydrogen) this would simplify the conversion because the supply and recharge points would be everywhere in the form of electric stations, therefore this can take from 10 to 15 years for manufacturers to fully overhaul and for sufficient backup power supply infrastructure [11,54].…”
Section: Discussionmentioning
confidence: 99%
“…This will require changes in the energy supply infrastructure. However, if all transport vehicles can run on batteries (electric and/or hydrogen) this would simplify the conversion because the supply and recharge points would be everywhere in the form of electric stations, therefore this can take from 10 to 15 years for manufacturers to fully overhaul and for sufficient backup power supply infrastructure [11,54].…”
Section: Discussionmentioning
confidence: 99%
“…It is a significant advantage for using these turbines in residential areas. Nemati [16] and Abid et al [17] showed that the combination of Savonius and Darrieus turbines improves the self-starting ability. Singh et al [18] also investigated self-starting performance for a three-bladed HDWT.…”
Section: Introductionmentioning
confidence: 99%